Heteroaggression and self-harm causal attributions in young university students: An analysis by sex - Valdez Medina , José Luis (Consorcio de Universidades Mexicanas A.C., 2016)
This research aims to identify behaviors heteroaggression and more frequent self-harm in young university students. To do this, we worked with 250 students between 18 and 25 years old, chosen through a non probabilistic intentional sampling. To whom were administered the questionnaire aggressive and self-aggressive Valdez-Medina (2015) which showed that 66% of participants have implemented the heteroaggression, the main reasons for this action: self-defense, displeasure, and intolerance towards the other person. Similarly, it was observed that 59.6% of respondents have self- declared assaulted at some point in their life, that to feel frustrated, angry and stressed. They are noting that these acts were carried out in both sexes by the way: physical, verbal and psychological, which allowed them to release their anger and achieve tranquility and relief. These results led to the conclusion that experimentation of negative emotions of hate and frustration, are associated with the presence of hetero-aggressive behavior and self, both men and women. And that aggression and self- injury was made by the participants adaptive court, as their behavior, seeking to preserve or restore the state of peace or lost balance.